Translation in Global News: Proceedings of the Conference held at the University of Warwick, 23 June 2006 - Conway, Kyle; Bassnett, Susan (Université d'Ottawa | University of Ottawa, 2006)
In 2006, the University of Warwick hosted a conference on the theme "Translation in Global News." This book, one of the first in the field of news translation, includes its proceedings. Contributors include Susan Bassnett, Yves Gambier, Martin Montgomery, Miren Gutiérrez, Sara Bani, Kyle Conway, Claire Tsai, M. Cristina Ciamott, Paule Salerno-O’Shea, Suvi Hautanen, and Stella Sorby.
Keywords: News translation; Translation; News